Information Security Issues In Automation Of Accounting In The Public Sector - Turdiyeva, Bakhtikhon Mukhamadjonovna (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2026)
This article highlights the relevance and importance of ensuring information security in the process of automating accounting in the public sector. The issues of maintaining the confidentiality, integrity and continuity of financial information in automated accounting systems are analyzed from a scientific, theoretical and practical perspective. Also, based on the experience of foreign countries, information security mechanisms used in the automation of accounting in the public sector are considered and the possibilities of their implementation in national practice are substantiated. The results of the study serve to increase the reliability of automated accounting systems and enhance the efficiency of financial management.